Excitation temperatures in plasma of underwater disharges between iron granules - Murmantsev, A.; Veklich, A.; Boretskij, V. (Вопросы атомной науки и техники, 2020)
This paper deals with development of optical emission spectroscopy techniques for diagnostic of underwater discharge plasma between iron granules. The difficulties in selection of iron spectral lines, as well as the approximation of their profiles for determination of excitation temperature are discussed. A method of spectral lines resolving with close wavelengths is considered. Simulation of a narrow rangeof the plasma emission spectrum is carried out to estimate the excitation temperatures in underwater discharge plasma.